2021
DOI: 10.1093/neuros/nyab079
|View full text |Cite
|
Sign up to set email alerts
|

Nonunion Rates After Anterior Cervical Discectomy and Fusion: Comparison of Polyetheretherketone vs Structural Allograft Implants

Abstract: BACKGROUND Although advances in implant materials, such as polyetheretherketone (PEEK), have been developed aimed to improve outcome after anterior cervical discectomy and fusion (ACDF), it is essential to confirm whether these changes translate into clinically important sustained benefits. OBJECTIVE To compare the radiographic and clinical outcomes of patients undergoing up to 3-level ACDF with PEEK vs structural allograft i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 21 publications
1
26
1
Order By: Relevance
“…Furthermore, the use of corticocancellous allografts need not be avoided due to its similar or better fusion rate compared with that of other interbody spacers, as demonstrated in previous studies, and clinical results were not adversely affected, as demonstrated in the present study. 32 Still, caution is needed when using corticocancellous allografts owing to the high rate of graft resorption or fracture and negative implications of these risks on radiographic outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, the use of corticocancellous allografts need not be avoided due to its similar or better fusion rate compared with that of other interbody spacers, as demonstrated in previous studies, and clinical results were not adversely affected, as demonstrated in the present study. 32 Still, caution is needed when using corticocancellous allografts owing to the high rate of graft resorption or fracture and negative implications of these risks on radiographic outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the use of corticocancellous allografts need not be avoided to its similar or better fusion rate compared with that of other interbody spacers, as demonstrated in studies, and clinical results were not adversely affected, as demonstrated in the present study. 32 Still, caution is needed when using corticocancellous allografts owing to the high rate of graft resorption or fracture and negative implications of these risks on radiographic outcomes. Although improvement of patient symptoms is the primary purpose of the operation, attempts should be made to decrease the rate of radiographic complications such as pseudarthrosis and subsidence, since these complications can occasionally lead to revision operations or worse clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous researchers showed that the proportion of nonunion in cages after ACDF was <10%. [ 4 , 6 , 11 ] Nonunion after spinal fusion procedures can result in recurrent pain, radiculopathy, and kyphotic deformity. However, its risk factors are controversial.…”
Section: Discussionmentioning
confidence: 99%
“…Although the cage nonunion is not very high, it may cause serious consequences, including recurrent pain, radiculopathy, and kyphotic deformity. [4][5][6] Several studies showed that implant material, age, low bone mineral density, smoking status, low level of vitamin D and multilevel ACDF were risk factors for cage nonunion. [7][8][9] However, its risk factors are controversial (Table S1, Supplemental Digital Content 1, http://links.lww.com/MD/H389).…”
Section: Introductionmentioning
confidence: 99%